PENGARUH LATIHAN CATCH AND DROP PUSH UPS TERHADAP POWER OTOT LENGAN DAN BAHU PADA ATLET RANDORI PUTRA KELOMPOK DEWASA SHORINJI KEMPO DOJO RUMBAI PEKANBARU - Sri Rahayu; Slamet '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on observation that I did when randori adult men athlete of Dojo Rumbai group Shorinji Kempo Pekanbaru following various championships like: the provinces championship in the town of Dumai in December 2015 years ago, and then national championship in Surabaya 29-31 July 2016, most of them do attacks, but the power of arm and shoulder muscle still weak or less powerfull and he can still do a counter attack, so that they can’t get points and having the time compete. This research purpose want to know the effect of of Catch and Drop Push Ups exercise toward the power of arm and shoulder muscle of Randori adult men athlete of Dojo Rumbai group Shorinji Kempo Pekanbaru. Forms of this research is the experimental treatment (Experimental), with sampel of 5 people. Were obtained and collected through the pree test and post test before and after Catch and Drop Push Ups exercise using instrument Two Hand Medicine Ball Put test, which aims to measure the power of arm and shoulder muscle. After that, the data is processed with statistical, normality test with lilifors test at significance level α (0.05). The hypothesis is the effect of exercise Catch and Drop Push Ups to the power of arm and shoulder muscle. Based on t test analysis produces Ttabel Thitung of 3.61 and 2.132, meaning Thitung> Ttabel. Based on the analysis of statistical data, there are an average Pree-test of 4,078 and an average post-test 4,396, then the data is normal. Thus, there Effect of Catch and Drop Push Ups exercise toward the power of arm and shoulder muscle of randori adult men athlete of dojo rumbai group shorinji kempo pekanbaruKeywords : Catch and Drop Push Ups, The Power Of Arm And Shoulder Muscle